Pro: Steroids Can Be Withdrawn After Transplant in Recipients With Autoimmune Hepatitis. Issue 8 (24th August 2018) - Kalra, Avash; Burton, James R.; Forman, Lisa M.
Abstract: Corticosteroids have been a mainstay of immunosuppression following liver transplantation. However, evolution in the field of transplant immunology has produced steroid‐free options, resulting in most transplant centers weaning steroids after transplant within days to months—an evidence‐based management decision. Patients with autoimmune hepatitis (AIH), however, receive corticosteroids prior to transplant. This raises the question of whether these patients should also be weaned from corticosteroids. In this review, we discuss the benefits of avoiding steroid use in this population of patients—an approach that not only avoids the adverse effects of corticosteroids but does so without risking graft failure from recurrent AIH or from acute cellular rejection.